2009
DOI: 10.1501/egifak_0000001141
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Suitability of Practices in Teacher Training Programs for the Constructivism Depending on the Teacher Trainees’ Views

Abstract: ABSTRACT:The aim of this study was to put forward the teacher trainees' views about how much the constructivist practices are carried out in the instructional planning, teaching-learning and evaluation processes in teacher training programs. In this survey study, a scale developed by the researcher was used. The study group was composed of 328 seniors at Anadolu University Education Faculty in 2004-2005 academic year. The analysis of the data was carried out by frequency, percent, t test, variance analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The effect of teacher educators over teacher candidates has not been explored (Yıldırım 2013), and there is limited number of studies examining faculty members at education faculties in Turkey. Mostly employing quantitative research designs, these studies (Aslan & Yakar, 2011;Aydın, Demirkasımoğlu & Alkın, 2012;Bayram, 1992;Deryakulu 1992;Ergün, Duman, Kıncal & Arıbaş, 1999;Kavak, 1986;Keçeci & Taşocak, 2009;Kumral, 2009;Oğuz, 2009;Oktar & Yazçayır, 2008;Saylan & Uyangör, 1998;Taş, 2009;Yüksel, 2002) have focused on teacher educators in terms of various characteristics (e.g. feedback and correction behaviors, teaching qualities, effective or ideal teacher characteristics, competencies, communication skills, academic ethics).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of teacher educators over teacher candidates has not been explored (Yıldırım 2013), and there is limited number of studies examining faculty members at education faculties in Turkey. Mostly employing quantitative research designs, these studies (Aslan & Yakar, 2011;Aydın, Demirkasımoğlu & Alkın, 2012;Bayram, 1992;Deryakulu 1992;Ergün, Duman, Kıncal & Arıbaş, 1999;Kavak, 1986;Keçeci & Taşocak, 2009;Kumral, 2009;Oğuz, 2009;Oktar & Yazçayır, 2008;Saylan & Uyangör, 1998;Taş, 2009;Yüksel, 2002) have focused on teacher educators in terms of various characteristics (e.g. feedback and correction behaviors, teaching qualities, effective or ideal teacher characteristics, competencies, communication skills, academic ethics).…”
Section: Introductionmentioning
confidence: 99%
“…That's why, the effect of these approaches and theories on teacher training programs is undeniable. While individual based learning is replacing the concept of knowledgebased teaching-learning, in terms of the notion of teacher training, a variety of different approaches have emerged namely "behaviouristic approach" supporting the idea that learning occurs via knowledge transfer; "field expert" approach supporting the efficiency of knowing subject matter; "experience/practice-based approach" supporting that teacher should gain more and more experience in order for learning to come true, "constructivist approach" totally centralising the learner while giving the teacher a guidance role (YalazAtay, 2003;Gökçe and Demirhan, 2005;Ekiz, 2006;O uz, 2009;Y ld r m, 2011) Primary teaching programs based on constructivist approach have started to be implemented in Turkey since 2005-2006 academic year. It can be suggested that the situation required a need to train teachers that will have the qualities to employ these constructivist approach based programs.…”
Section: Introductionmentioning
confidence: 99%